2019
DOI: 10.1002/minf.201900134
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Health Effects of Food Peptides and Elucidation of the Mode‐of‐action Using Multi‐task Graph Convolutional Neural Network

Abstract: Food proteins work not only as nutrients but also modulators for the physiological functions of the human body. The physiological functions of food proteins are basically regulated by peptides encrypted in food protein sequences (food peptides). In this study, we propose a novel deep learning-based method to predict the health effects of food peptides and elucidate the mode-of-action. In the algorithm, we estimate potential target proteins of food peptides using a multi-task graph convolutional neural network,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…170 For example, Fukunaga et al reported the antihypertensive and hypoglycemic effects of food peptides and the anticancer effects of several food peptides. 171 Peptidespecific Maillard reaction products (MRPs) have a unique flavor in food processing and storage due to their unique molecular structure and formation mechanism. In addition, these MRPs also have antioxidant, antibacterial, antihypertensive, anti-inflammatory, and other biological activities.…”
Section: Other Functional Peptidesmentioning
confidence: 99%
“…170 For example, Fukunaga et al reported the antihypertensive and hypoglycemic effects of food peptides and the anticancer effects of several food peptides. 171 Peptidespecific Maillard reaction products (MRPs) have a unique flavor in food processing and storage due to their unique molecular structure and formation mechanism. In addition, these MRPs also have antioxidant, antibacterial, antihypertensive, anti-inflammatory, and other biological activities.…”
Section: Other Functional Peptidesmentioning
confidence: 99%
“…Deep learning has also been used in peptide drug research, such as for predicting health effects using peptide chemical structure and antimicrobial activity using amino acid sequences [21,22]. Automatic peptide-generation models using recurrent neural network, VAE, and GAN have been developed to generate peptides with antimicrobial activity [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, for data with irregular graph structures, the surrounding structure of each data node may be unique, which makes the CNN and RNN fail instantaneously, so Bruna et al [14] proposed the GCN. GCN can effectively process irregular graph data, fully learn node features and edge information representing node association in the graph, extract hidden and weak features, and express the index information in the graph [15,16]. It should be noted that the calculation of the next-layer feature of a node is only related to itself and its neighbor nodes in GCN.…”
Section: Introductionmentioning
confidence: 99%